Sixty years of anisotropy of magnetic susceptibility in deformed sedimentary rocks - Parés, Josep M. (Frontiers in Earth Science, 2015)
The use of the Anisotropy of Magnetic Susceptibility (AMS) has become a rather common practice in Earth Sciences since the pioneer note by Graham (1954). The versatility of the technique, and the rapidness in obtaining and processing AMS data largely improved in the past thirty years, and has generated a wealth of literature, notably on mudrock fabrics. The assessment of the current trends in magnetic fabric studies reveals that AMS has one of its largest potential in sedimentary rocks from structural settings where the ductile component of deformation is cryptic or hindered by the brittle component. Abundant evidence provided by AMS data reveal that deformation extents beyond the deformation or cleavage front in contractional settings, including fold-and-thrust belts and active accretionary prisms, configuring magnetic fabrics as a standard method for fabric quantification in deformed sedimentary rocks.